2011
DOI: 10.1016/j.bodyim.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender on the assessment of body checking behavior

Abstract: Body checking includes any behavior aimed at global or specific evaluations of appearance characteristics. Men and women are believed to express these behaviors differently, possibly reflecting different socialization. However, there has been no empirical test of the impact of gender on body checking. A total of 1024 male and female college students completed two measures of body checking, the Body Checking Questionnaire and the Male Body Checking Questionnaire. Using multiple group confirmatory factor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
(51 reference statements)
4
28
0
8
Order By: Relevance
“…Alfano et al 12 sugerem o uso de instrumentos específicos para cada sexo (BCQ -mulheres; MBCQ -homens) por causa das idiossincrasias encontradas quanto à expectativa de corpo e rituais de autoavaliação dele. Esta pesquisa teve esse cuidado metodológico ao utilizar instrumentos específicos e identificou maior frequência de checagem entre as mulheres, o que reforça o fato de estas apresentarem comportamento mais frequente de autoavaliação do corpo, geralmente acompanhado de insatisfação corporal, quando comparadas aos homens 12 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Alfano et al 12 sugerem o uso de instrumentos específicos para cada sexo (BCQ -mulheres; MBCQ -homens) por causa das idiossincrasias encontradas quanto à expectativa de corpo e rituais de autoavaliação dele. Esta pesquisa teve esse cuidado metodológico ao utilizar instrumentos específicos e identificou maior frequência de checagem entre as mulheres, o que reforça o fato de estas apresentarem comportamento mais frequente de autoavaliação do corpo, geralmente acompanhado de insatisfação corporal, quando comparadas aos homens 12 .…”
Section: Discussionunclassified
“…Ações no sentido de diminuição desse comportamento em pacientes com transtornos alimentares têm sido frequentes 9,10 e são apontadas como alternativa de intervenção para o distúrbio de imagem corporal 8 . O comportamento de checagem corporal também está presente na população não clínica 11,12 . Os resultados apontam para uma influência direta da checagem corporal na atenção seletiva do indivíduo para o seu corpo, com aumento da insatisfação sobre ele 11 .…”
Section: Introductionunclassified
“…Meanwhile, moderate body-checking was present in 22.43% and 14.43% of females and males, respectively. By using the same instruments applied in this research (BCQ and MBCQ), Alfano et al 15 identified significant differences in the frequency of body-checking behavior between genders. University female students showed higher frequency of body-checking behavior than males.…”
Section: Discussionmentioning
confidence: 99%
“…Body-checking behavior is related to the adoption of inappropriate eating behaviors, which is known to be harmful to health, such as extreme food restriction [12][13][14][15][16] . Patients diagnosed with anorexia nervosa and bulimia nervosa demonstrate a higher frequency of this behavior than a non-clinical population [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation